Understanding The Role of Citizen Journalism in Social Media: A Phenomenological Approach to The 'Medan Talk' Instagram Account - diaz satria; Alifah Rose Wiana (Yayasan Al'Adzkiya Rantauprapat, 2025)
The rapid development of information and communication technology (ICT) has had a significant impact on people's lifestyles, with the transition from the industrial era to the information society. This study highlights the role of social media, especially Instagram, as a major source of information in the digital era, which can surpass traditional media. The phenomenon of citizen journalism, defined as public participation in the gathering, reporting, analysis and dissemination of news, has empowered individuals to become active contributors to the dissemination of information. This research examines the application of citizen journalism through the Instagram account @MedanTalk, a leading social media platform in Medan, Indonesia. Using qualitative methods such as observation, interviews and documentation, this study analyses how @MedanTalk collects, verifies and disseminates information from the community. The results show that @MedanTalk successfully fills the gap in local news, especially regarding traffic conditions, public issues and social events, while encouraging community participation. Despite these benefits, challenges such as content validity and ethics in reporting remain a concern. Addressing these challenges through rigorous content management and promoting media literacy among users can increase the credibility and impact of these platforms. This research concludes that citizen journalism, as demonstrated by MedanTalk, plays an important role in creating an inclusive and participatory information ecosystem in the digital age.